AI Literacy, Technical Skills, and Ethical Awareness in Predicting Students’ Learning Performance - Devi Miftahul Jannah; Syamsul Huda; Muhamad Yasin; Sanatang Sanatang; M Miftach Fakhri; Syahid Nur Wahid; Andi Baso Kaswar; Soeharto Soeharto; Stephen Amukune (Online Learning In Educational Research (OLER), 2026)
The increasing integration of AI systems into various sectors of the economy has also raised ethical concerns. Even as education in AI has developed to ensure that learners have the appropriate technical skills, the existing systems have failed to address the issue of ethics. As a way of addressing the problem, the current study aims at investigating learning about AI literacy and ethical reasoning. The author in this research applied the Partial Least Squares Structural Equation Modeling (PLS-SEM), from a questionnaire consisting of 400 university students (conducted of informatics and computer engineering department) to examine the relevance of AI literacy (AI-DAIB theories/basics), technical skills (TS), learning performance (LPER and EAI as moderating effect on AI perception (AIP). The findings found interesting result that AI literacy and technical skills have significant effects on learning performance and the moderating effect of AI ethics also increases the added value. This study indicates the need for a wider framework of all educational activities focusing on the development of technical skills, AI literacy and (semi)AI ethics to respond effectively to gaps in both development and moral responsibility of AI technologies